Child injury deaths linked with adult alcohol consumption: A time series analysis - Laslett, Anne-Marie; Jiang, H.; Chikritzhs, Tanya (Elsevier Ireland Ltd, 2018)
Objective: This paper aims to quantify the population-level associations between child injury deaths and adult (aged 15+ years) per capita alcohol consumption (PCC) and between child injury deaths and the impact of major alcohol and safety policy changes in Australia. Methods: All child deaths due to external causes during 1910–2013, and child deaths due specifically to road crashes, assaults, suicide and other external causes, were obtained from the Australian Institute of Health and Welfare. Child (0–14 year) mortality rates were analysed in relation to PCC using an Autoregressive Integrated Moving Average model. Results: A positive association between PCC and overall child external mortality was identified. The estimated coefficient was 0.326 (p = .002), indicating that a 10% decrease in PCC was associated with a 3.3% reduction in child injury mortality. A positive association was identified for road traffic and other child injury mortality, but not assault injuries. The introduction of compulsory seatbelt legislation in combination with random breath testing was associated with a reduction in overall injury and road traffic child mortality. Decreasing the legal drinking age was associated with an increase in the rate of other external-cause child mortality. Conclusion: Reducing PCC in Australia is likely to result in a small but significant reduction in the injury mortality rate of children aged 0–14 years.